A Rare Case Report of Giant Cervical Angiomatous Polyp - R.K.Tandon; Nidhi Patel; Shivani Vora (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cervical polyps which are giant are less commonly seen in day to day patient examination. It is calledgiant when it is of more than 4 cm. It can mimic cervical cancer also. This case which we are presentinghere is about the cervical angiomatous giant polyp in a woman who was presented with pain in abdomenand increased flow of menses since 1 month. Tissue section was studied and diagnosed as giant cervicalangiomatous type polyp which is seen very very less commonly